Back Massage and Noni Fruit (Morinda citrifolia) Reduced Blood Pressure in People with Hypertension - Ni Kadek Yuni Lestari; I Ketut Suardana; Ni Wayan Trisnadianti (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2017)
Hypertension is an increase in blood pressure caused by decreased elasticity of blood vessels and that often found in the elderly. Blood pressure is the resistance of blood vessels when the blood flows throughout the body. Treatment of hypertension can be treated with non-pharmacological therapy such as back massage and drink noni fruit (Morinda Citrifolia) processed. Back massage can decrease blood pressure caused by the presence of mechanoreceptor as vasodilators. Noni fruits have scopoletin as vasodilators and xeronin as deuretics. This study aims to determine the effect of back massage and consuming processed from noni fruit to blood pressure in hypertension at Clinical Region of Public Health Center II North Denpasar. This research using Quasi-experiment with nonequivalent control group design. Sample of 26 respondents was divided into the treatment (intervention) group and the control group. Results of the Paired T-test that systolic pressure p=0.001; Diastolic pressure p=0.003; And Mean Arterial Pressure p=0,001. Result of the Independent T-test that systolic pressure p=0,048; Diastolic pressure p=0.011; And Mean Arterial Pressure p=0.005 (≤α=0,05), the results showed that there was significant effect of back massage and noni fruit processed to decreased blood pressure in people with hypertension. Expected back massage and noni fruit preparations can be used as an alternative to decreasing blood pressure in people with hypertension.